2017
DOI: 10.1007/s10750-017-3364-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a small-scale riverine obstacle on the upstream migration of Atlantic Salmon

Abstract: The behaviour of returning Salmo salar (Linnaeus, 1758) approaching, and attempting to pass low-head weirs remains relatively unknown. A radio telemetry array was created at a low-head weir to enable the behaviour of S. salar (n = 120) to be observed as they approached and attempted to pass the barrier. The majority of fish successfully passed the barrier on their first or second attempt, some individuals required 11 attempts prior to successful passage occurring. Mean delay at the barrier per fish was 47.8 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
0
25
1
Order By: Relevance
“…The majority of migratory alleles (67%-72%) in the system were found in the reach of stream below this partial barrier. While other studies have documented that complete barriers select against anadromy, leading to divergence in O. mykiss populations distributed above and below barriers (Leitwein, Garza, & Pearse, 2017;Pearse et al, 2009), our study provides an example of the lesser-studied effects of small, partial barriers on the distri- or small diversion dams (Newton, Dodd, Barry, Boylan, & Adams, 2018;. Apgar et al (2017) Here, we demonstrate that landscape permeability, including distance upstream and partial barriers, determines the potential for migratory animals to access certain habitats and thus the spatial distribution of migratory genotypes.…”
Section: Distance and Permeable Barriers Influence Distribution Of mentioning
confidence: 50%
See 1 more Smart Citation
“…The majority of migratory alleles (67%-72%) in the system were found in the reach of stream below this partial barrier. While other studies have documented that complete barriers select against anadromy, leading to divergence in O. mykiss populations distributed above and below barriers (Leitwein, Garza, & Pearse, 2017;Pearse et al, 2009), our study provides an example of the lesser-studied effects of small, partial barriers on the distri- or small diversion dams (Newton, Dodd, Barry, Boylan, & Adams, 2018;. Apgar et al (2017) Here, we demonstrate that landscape permeability, including distance upstream and partial barriers, determines the potential for migratory animals to access certain habitats and thus the spatial distribution of migratory genotypes.…”
Section: Distance and Permeable Barriers Influence Distribution Of mentioning
confidence: 50%
“…While other studies have documented that complete barriers select against anadromy, leading to divergence in O. mykiss populations distributed above and below barriers (Leitwein, Garza, & Pearse, ; Pearse et al, ), our study provides an example of the lesser‐studied effects of small, partial barriers on the distribution of migratory genotypes in O. mykiss. Small barriers are common across the landscape (Januchowski‐Hartley et al, ), and include natural features, such as tributary confluences or waterfalls like those studied here, but also include artificial landscape features, such as road crossings (Benton, Ensign, & Freeman, ) and weirs, or small diversion dams (Newton, Dodd, Barry, Boylan, & Adams, ; Weigel, Connolly, & Powell, ). Apgar et al () estimated many small barriers can have a similar effect as a single larger barrier in reducing the migratory allele frequency in O. mykiss .…”
Section: Discussionmentioning
confidence: 99%
“…Newton et al . () found that smaller salmon exhibited greater passage success at a manmade weir on the River Foyle, Ireland, and postulated that this was a selective response to the obstacle because smaller fish could better negotiate the shallow weir apron. The Salmon Leap waterfall has been a long‐term natural factor on the River Bush that has structured the upstream fish community by blocking access for anadromous brown trout and marine lamprey Petromyzon marinus L. 1758 and has probably influenced the evolutionary development of the local salmon population.…”
Section: Discussionmentioning
confidence: 99%
“…This approach would be applicable in many other situations, especially those involving unique natural barriers. Preliminary studies are particularly useful since most obstacles display highly variable passage windows influenced by sitespecific parameters (Newton et al, 2018). Modern fish telemetry methods are well suited to studying the migratory activity of fish at riverine barriers and can be used to develop effective, site specific, fish-passage solutions.…”
Section: Discussionmentioning
confidence: 99%
“…This design reconfiguration enables water to pass over the ramp, not generating a waterfall [5,10], a condition that may afford a more holistic negotiation by fish [5,13]. Nevertheless, fish swimming abilities, which are closely related to fish guilds and body size [14][15][16][17], and hydrodynamic conditions, such as water depth, discharge, and turbulence present over the ramp and in the vicinity of the structure [5,[18][19][20], are key factors that influence the permeability of such structures to fish movements.The addition of substrates to instream obstacles and fish transposition devices, commonly referred to as retrofitting, has been considered a useful management solution to enhance upstream fish passage [5,[21][22][23][24][25][26][27][28]. The placement of substrates in culverts to mimic natural stream conditions and facilitate fish passage has been successfully implemented since the early 1970s [29].…”
mentioning
confidence: 99%